Creative economy improvement: Optimizing tourism potential through institution linking and branding - Muhammad Eko Atmojo; Nasrullah Nasrullah; Vicky Alfitra Perdana (University of Merdeka Malang, 2024)
Tourism villages play a crucial role in national economic growth. However, despite their potential, they often face institutional challenges and lack integration in information technology use, hindering economic progress. Hargorejo tourism village exemplifies these issues, with untapped potential and limited managerial competence hindering economic growth. This community service initiative aims to address these challenges by enhancing understanding of institutional design and emphasizing the importance of branding for each business unit. Through managerial and administrative training and group discussions, the service seeks to strengthen institutions. Additionally, assistance in creating the tourism village website, Kawitarjo.id, aims to support expanded tourism branding for sustainable economic improvement. The outcome includes the establishment of a digital forum, integrating tourism potential, and enhancing managers' understanding of implementing tourism branding through digital media. This comprehensive approach contributes to stronger institutions and increased managerial comprehension of tourism village duties, fostering economic growth in the creative industry sector, and benefiting society as a whole. Ultimately, it aims to empower local communities and promote inclusive economic development.